Lifelong dream of performing the Hajj.How happy will you be when you performing the pilgrimage? The experiences of Malaysian Hajj pilgrims - Ayob, Salahuddien; Mohd Hashim, Intan Hashimah; Ahmad Hatta, Zulkarnain; Sulong, Jasni (2014)
Hajj is once-in-a-lifetime pilgrimage required for every able-bodied Muslims who can afford it.To perform the hajj is a lifelong dream for most Muslims.Anecdotal evidence by those who have completed the hajj describe it as a psychologically and spiritually fulfilling journey, that lead to some degree of positive transformation at the conclusion of it.The present study describes the relationships between cognitive and affective aspects of subjective wellbeing, as reported by the Malaysians who were performing the pilgrimage.With support and permission from Tabung Haji Malaysia, questionnaires were distributed during the 2013 hajj pilgrimage period.300 male and female Malaysian pilgrims responded to Malay language version of Satisfaction with Life Scale (Pivot & Diener, 1993) and Positive and Negative Affect Schedule (Watson, Clark, and Tellegen, 1988).The two scales describe an overall picture of happiness, laymen’s term for subjective well-being, among the pilgrims. Data indicates that the Malaysian Hujjaj are happier than other sample tested using the same measures.Analysis of data showed that these cannot be generally attributed to gender, age, formal religious education, previous Hajj experience, previous experience in visiting Makkah or performing the umrah. These indicate the need for further studies on this matter.